Insights into the role of Cerium-based inhibitor in improving the anti-corrosion performance of ZnAl alloy coated carbon steel substrate - Nguyen, Anh Son; Pham, Thu Thuy; Nguyen, Thuy Duong; Vuong, Thi Vy Anh; Nguyen, Thi Thu Trang (Communications in Physics, 2026)
This study quantitatively investigates the physicochemical evolution of protective layers on ZnAl alloy coated carbon steel, focusing on the inhibitory performance of cerium-based compounds Ce(NO3)3 in a chloride medium. A combination of electrochemical techniques, Open Circuit Potential monitoring, Potentiodynamic Polarization and Electrochemical Impedance Spectroscopy, was employed to demonstrate the addition of Ce3+ ions significantly enhances corrosion resistance. For the uninhibited solution, EIS modeling consistently revealed a continuous increase in capacitive elements and a drastic decline in resistive elements. signifying physical barrier breakdown. The optimal concentration, 10-4 M, fostered the growth of a stable, progressively densifying Ce-enriched layer. This layer maintained high Rct (up to 8553 Ω.cm2), confirming its superior physical barrier integrity. Surface morphology analysis using Scanning Electron Microscopy corroborated this finding, revealing the formation of a homogeneous, crack-free cerium containing film structure at this optimal concentration. Conversely, the 5×10-4 M concentration led to long-term failure, attributed to the formation of a mechanically weak, heterogeneous outer deposit prone to cracking. These findings quantitatively establish the relationship between cerium concentration, the resulting film’s physical structure, and its long-term anti-corrosion durability.